A scale development study on democratic attitude among third and fourth grade students - Cüneyt Akar; Ufuk Uluçınar (Journal of Pedagogical Research, 2023)
This study aims to develop an instrument that measures democratic attitudes levels in primary school students in third and fourth grades. This study involved 591 students (302 for exploratory factor analysis, 289 for confirmatory factor analysis) enrolled in the 3rd and 4th grades. A literature review was conducted to prepare the scale items, and a pool of 32 items was created. A face and content validity assessment was performed by taking the opinions of four educators who are experts in classroom education and social studies education. A construct validity test was conducted on 302 students. The exploratory factor analysis resulted in a scale with three dimensions and 15 items. Confirmatory factor analysis was conducted with a group of 289 students using the scale. Based on the confirmatory factor analysis, the 15-item and 3-dimensional structure of the scale was compatible with the collected data. According to the results, the reliability coefficient of the scale was .85. Thus, the scale can be considered a valid and reliable tool for measuring democratic attitudes among primary school students in third and fourth grades.